Significant Structural Alterations and Functional Connectivity Alterations of Cerebellar Gray Matter in Patients With Somatic Symptom Disorder - Liang, Huai-Bin; Dong, Liao; Cui, Yangyang; Wu, Jing; Tang, Wei; Du, Xiaoxia; Liu, Jian-Ren (Frontiers in Neuroscience, 2022)
Objective Recent studies have revealed a strong association between the cerebellum and psychiatric disorders. However, the structural changes in the cerebellar regions and functional connectivity (FC) patterns in patients with somatic symptom disorder (SSD) have not been elucidated. Methods Thirty-seven patients with SSD (29 drug-naive and 8 medicated patients) and 37 sex- and age-matched healthy controls (HCs) were recruited and underwent resting-state functional magnetic resonance imaging scans. The spatially unbiased infratentorial (SUIT) cerebellar atlas-based voxel-based morphometry was used to investigate the changes in cerebellar regional gray matter (GM). Seed-based FC was further computed to explore the pattern of abnormal FC across the whole brain. Correlations were calculated to investigate the relationship between cerebellar structural (and FC) changes and clinical characteristics. Results After controlling for age, sex, total intracranial volume, medication, and mean FD covariates, all patients with SSD had increased mean GM volume (GMV) in the posterior lobules of the cerebellum bilaterally when compared with HCs, specifically, in the bilateral cerebellar crura I and II. Patients with SSD showed significantly stronger FC between the right crura I and II and bilateral precuneus inferior parietal region, and postcentral gyrus, extending to the superior parietal lobe, cingulate gyrus, and the white matter subgyral. In addition to the two clusters, right lingual gyrus was also a surviving cluster with significantly higher FC. Partial correlation analysis revealed that the degree of regional GMV increases in the two significant clusters and the Hamilton Depression Scale (HAMD) score was negatively correlated. Moreover, the FC of right crura I and II with the left parietal lobe and right lingual gyrus were also negatively associated with the HAMD score. Conclusions SSD exhibited significant microstructural changes and changes in FC pattern in the posterior cerebellar lobe. These results shed new light on the psychological and neural substrates of SSD and may serve as a potential treatment target for SSD based on the cerebellar area.